Comparative Study of Different Diets-Induced NAFLD Models of Zebrafish - Chen, Bo; Zheng, Yang-Min; Zhang, Jing-Pu (Frontiers in Endocrinology, 2018)
Dietary composition has important impact on nonalcoholic fatty liver disease (NAFLD). The purpose of this study was to explore the relationship between NAFLD and major dietary components using zebrafish larvae fed different diets. Zebrafish larvae fed with high cholesterol (HC), high fructose (HF) and extra feeding (EF) diets for 10 days displayed varying degrees steatosis. The incidence and degree of steatosis were the most severe in the EF group. A HC diet severely promoted lipid deposits in the caudal vein. The triglyceride and glucose contents of zebrafish significantly increased in the HF and EF groups compared with the control group. Moreover, the mRNA expression of oxidative stress gene gpx1a, endoplasmic reticulum stress genes ddit3 and grp78, inflammatory genes tnfa, glucose metabolism genes irs2, glut1 and glut2, and lipid metabolism genes cidec, chrebp, ppara and cpt1a were significantly increased in the HF group. The HC diet was associated with upregulation of grp78, and downregulation of irs2, glut1 and glut2. The mRNA expression of lipogenesis and glucose metabolism associated genes were decreased in the EF group. In addition, the autophagy associated genes atg3, atg5, atg7 and atg12, and protein expression of ATG3 and LC3BII were reduced and P62 were elevated in the HC group. We also performed comparative transcriptome analysis of the four groups. A total of 2492 differentially expressed genes were identified, and 24 statistically significant pathways were enriched in the diet treatment groups. This study extends our understanding of the relationships between diet ingredients and host factors that contribute to the pathogenesis of NAFLD, which may provide new ideas for the treatment of NAFLD.